2014
DOI: 10.3896/ibra.1.53.5.10
|View full text |Cite
|
Sign up to set email alerts
|

Towards integrated control of varroa: effect of variation in hygienic behaviour among honey bee colonies on mite population increase and deformed wing virus incidence

Abstract: SummaryHygienic behaviour in the honey bee, Apis mellifera, is the uncapping and removal of dead, diseased or infected brood from sealed cells by worker bees. We determined the effect of hygienic behaviour on varroa population growth and incidence of deformed wing virus (DWV), which can be transmitted by varroa. We treated 42 broodless honey bee colonies with oxalic acid in early January 2013 to reduce varroa populations to low levels, which we quantified by extracting mites from a sample of worker bees. We qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…Depending on varroa population increase, the level of mite kill from OA sublimation may be sufficient for annual treatment in a winter broodless period without the use of additional control measures in combination with hygienic behavior. This seems to be the case in the study location (Al Toufailia, Amiri, Scandian, Kryger, & Ratnieks, 2014), especially for colonies that are also hygienic. If this is not the case then additional varroa control methods may be necessary.…”
Section: Discussionmentioning
confidence: 63%
“…Depending on varroa population increase, the level of mite kill from OA sublimation may be sufficient for annual treatment in a winter broodless period without the use of additional control measures in combination with hygienic behavior. This seems to be the case in the study location (Al Toufailia, Amiri, Scandian, Kryger, & Ratnieks, 2014), especially for colonies that are also hygienic. If this is not the case then additional varroa control methods may be necessary.…”
Section: Discussionmentioning
confidence: 63%
“…Their overall appearance was similar to that of honey bee workers with overt symptoms of deformed wing virus (DWV) (Al Toufailia et al, 2014). However, cDNA generated from RNA extracted from pooled samples of workers from both the diseased colony and healthy S. depilis colonies did not amplify for primers of DWV-F2 (strain A) and DWV-R2a (strain B) (McMahon et al, 2015).…”
Section: Methodsmentioning
confidence: 78%
“…Worker honey bees showing hygienic behaviour detect and uncap cells containing dead and infected brood, and remove the contents from the colony (Rothenbuhler, 1964a,b). Hygienic behaviour has been shown to help control varroa mites, deformed wing virus (DWV), chalkbrood, and American foulbrood (Al Toufailia et al, 2014; Spivak and Gilliam, 1998a,b; Wilson-Rich et al, 2009). Hygienic behaviour is not learned, rather, it is an instinctive heritable trait controlled by multiple genetic loci (Jones and Rothenbuhler, 1964; Momot and Rothenbuhler, 1971; Rothenbuhler, 1964a,b; Wilson-Rich et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent studies indicate that tolerance to the deformed wing virus may be under genetic control (Khongphinitbunjongaet et al, 2015;Locke, Forsgren, & de Miranda, 2014). Al Toufailia Amiri, Scandian, Kryger, and Ratnieks (2014) found that worker bees from colonies that were more than 95% hygienic had significantly fewer mites and lower levels of RNA copies of DWV. The ideal situation for beekeepers would be a mite-resistant bee that is both tolerant to the damage caused by the mites and the diseases they vector.…”
Section: Discussionmentioning
confidence: 99%